Paleoproterozoic volcanism and rift basin evolution during Nuna assembly: Evidence from the Ingrid group, Labrador, Canada - Alana M. Hinchey; Nicole Rayner; Hamish Sandeman; Jared P. Butler; David Diekrup; Daniela Mendoza Marin (Precambrian Research, 2025)

Intercomparison of in-well, depth profile and online soil gas measurements for estimating petroleum natural source zone depletion rates: Will in-well gas samples suffice? - Greg B. Davis; John L. Rayner; Mike J. Donn; Trevor P. Bastow; Andrew Furness; Yasuko Geste; Andrew King (Journal of Hazardous Materials, 2025)

Around the World in 26 Million Years: Diversification and Biogeography of Pantropical Grass‐Yellow Eurema Butterflies (Pieridae: Coliadinae) - Jing V. Leong; Pável Matos‐Maraví; Rayner Núñez; Renato Nunes; Weijun Liang; Michael F. Braby; Tenzing Doleck; Kwaku Aduse‐Poku; Yutaka Inayoshi; Yu‐Feng Hsu; Niklas Wahlberg; Djunijanti Peggie; et al. (Journal of Biogeography, 2025)
Aim Grass‐yellow butterflies ( Eurema ) are a group of pantropical Pieridae distributed throughout Asia, Australasia, Africa and the New World. However, little is known about their diversification, including the biogeographic mechanism(s) explaining their circumglobal distribution. We present the first densely sampled, time‐calibrated phylogeny and biogeographic reconstruction of grass‐yellows to confirm the monophyly of the genera, re‐evaluate their taxonomy and infer the biogeographic events contributing to their worldwide distribution. Location Global tropics and subtropics. Taxon The butterfly tribe Euremini (Pieridae: Coliadinae). Methods We analysed up to 391 genetic loci from 126 samples of 66 ingroup species. Divergence dating was accomplished in a Bayesian phylogenetic framework using secondary calibration points, and maximum likelihood models of various biogeographic models were fitted to the data using the R package BioGeoBEARS. We used the best fitting model to estimate relative dispersal events with biogeographical stochastic mapping. Finally, we estimated branch‐specific speciation and extinction rates to assess the diversification history of the group. Results Different phylogenomic analyses converged on similar topologies with robust support. Grass‐yellows emerged ca . 26 Mya in the New World, and a single extant lineage dispersed to Asia in the early Miocene, where they diversified and dispersed to Africa and Australasia. The fastest rates of diversification occurred in the Old World tropics during the late Miocene. Many of the grass‐yellow genera were either paraphyletic or polyphyletic as traditionally circumscribed. To maintain nomenclatural stability, we place all grass‐yellows in Eurema sensu lato and recognise two subgenera: Eurema ( Abaeis ) and Eurema ( Eurema ). Main Conclusions Grass‐yellow butterflies originated in the Americas and attained their global distributional patterns via dispersal. The Indo‐Australian and Caribbean archipelagoes seem to have accelerated the diversification of the group, and movement in and out of these island regions was frequent. Although the traditional view of founder‐event speciation envisions migrants from large landmasses (‘mainland’) colonising smaller landmasses (‘islands’), we find that island to mainland dispersal and differentiation were equally or more common.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Natural Source Zone Depletion of crude oil, gasoline, diesel and aviation gasoline petroleum in the same soil/aquifer system – An intensive intercomparison field study and simulation - John L. Rayner; Mike J. Donn; Greg B. Davis; Trevor P. Bastow; Kaveh Sookhak Lari; Colin D. Johnston; Andrew King; Andrew Furness (Science of The Total Environment, 2024)

Population genomics of the ‘rediscovered’ threatened New Zealand storm petrel (Fregetta maoriana) support a single breeding colony - Anika N. Correll Trnka; Chris P. Gaskin; Matt J. Rayner; Brent Stephenson; Fiona Robertson; Bruce C. Robertson; Anna W. Santure (Conservation Genetics, 2024)

Advective and diffusive gas phase transport in vadose zones: Importance for defining vapour risks and natural source zone depletion of petroleum hydrocarbons - Kaveh Sookhak Lari; Greg B. Davis; John L. Rayner; Trevor P. Bastow (Water Research, 2024)

The E3 Ubiquitin Ligase SCF Cyclin F Promotes Sequestosome-1/p62 Insolubility and Foci Formation and is Dysregulated in ALS and FTD Pathogenesis - Jennilee M. Davidson; Sharlynn S. L. Wu; Stephanie L. Rayner; Flora Cheng; Kimberley Duncan; Carlo Russo; Michelle Newbery; Kunjie Ding; Natalie M. Scherer; Rachelle Balez; Alberto García-Redondo; Alberto Rábano; et al. (Molecular Neurobiology, 2023)
Amyotrophic lateral sclerosis (ALS)- and frontotemporal dementia (FTD)-linked mutations in CCNF have been shown to cause dysregulation to protein homeostasis. CCNF encodes for cyclin F, which is part of the cyclin F-E3 ligase complex SCF cyclinF known to ubiquitylate substrates for proteasomal degradation. In this study, we identified a function of cyclin F to regulate substrate solubility and show how cyclin F mechanistically underlies ALS and FTD disease pathogenesis. We demonstrated that ALS and FTD-associated protein sequestosome-1/p62 (p62) was a canonical substrate of cyclin F which was ubiquitylated by the SCF cyclinF complex. We found that SCF cyclin F ubiquitylated p62 at lysine(K)281, and that K281 regulated the propensity of p62 to aggregate. Further, cyclin F expression promoted the aggregation of p62 into the insoluble fraction, which corresponded to an increased number of p62 foci. Notably, ALS and FTD-linked mutant cyclin F p.S621G aberrantly ubiquitylated p62, dysregulated p62 solubility in neuronal-like cells, patient-derived fibroblasts and induced pluripotent stem cells and dysregulated p62 foci formation. Consistently, motor neurons from patient spinal cord tissue exhibited increased p62 ubiquitylation. We suggest that the p.S621G mutation impairs the functions of cyclin F to promote p62 foci formation and shift p62 into the insoluble fraction, which may be associated to aberrant mutant cyclin F-mediated ubiquitylation of p62. Given that p62 dysregulation is common across the ALS and FTD spectrum, our study provides insights into p62 regulation and demonstrates that ALS and FTD-linked cyclin F mutant p.S621G can drive p62 pathogenesis associated with ALS and FTD.

Homogenization of daily temperature and humidity series in the UK - Yuri Brugnara; Mark P. McCarthy; Kate M. Willett; Nick A. Rayner (International Journal of Climatology, 2023)
Building on previous experience with continental and global data sets, we use a quantile‐matching approach to homogenize temperature and humidity series measured by a network of 220 stations in the United Kingdom (UK). The data set spans 160 years at daily resolution, although data coverage varies greatly in time, space, and across variables. We use the homogenized data to analyse trends of the mean values as well as the lowest and highest quantiles of the distribution over the last 100 and 50 years. For the latter period, we find large regional differences, particularly between the southeastern and the northern part of the UK. The southeast has seen a faster warming, particularly for maximum temperatures in spring and summer, and a reduction of relative humidity; the northern mainland has become more humid and only slightly warmer. These differences become more evident for the highest quantiles and reflect a well‐known pattern of climate change affecting the extra‐tropics. Among the studied variables, the increases of wet bulb temperature and specific humidity are the most spatially homogeneous and are statistically significant for most stations in all seasons except winter.

Designing and managing biodiverse streetscapes: key lessons from the City of Melbourne - Hui-Anne Tan; Lee Harrison; Jeff Nelson; Maggie Lokic; John P. Rayner; Caragh G. Threlfall; Jessica Baumann; Adrian Marshall; Mark Callow; Jessica Peeler; Rebecca Korossy-Horwood; Chris Nicholson; et al. (Urban Ecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Kaiso is highly expressed in TNBC tissues of women of African ancestry compared to Caucasian women - Blessing I. Bassey-Archibong; Shawn M. Hercules; Lyndsay G. A. Rayner; Desiree H. A. Skeete; Suzanne P. Smith Connell; Ian Brain; Adetola Daramola; Adekunbiola A. F. Banjo; Jung S. Byun; Kevin Gardner; Jonathan Dushoff; Juliet M. Daniel (Cancer Causes & Control, 2017)

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Atmospheric inversions for estimating CO2 fluxes: methods and perspectives - P. Ciais; P. Rayner; F. Chevallier; P. Bousquet; M. Logan; P. Peylin; M. Ramonet (Climatic Change, 2010)

Oxidant Stress and Damage in Post-Ischemic Mouse Hearts: Effects of Adenosine - Benjamin Hack; Paul K. Witting; Benjamin S. Rayner; Roland Stocker; John P. Headrick (Molecular and Cellular Biochemistry, 2006)

Model–data synthesis in terrestrial carbon observation: methods, data requirements and data uncertainty specifications - M. R. Raupach; P. J. Rayner; D. J. Barrett; R. S. DeFries; M. Heimann; D. S. Ojima; S. Quegan; C. C. Schmullius (Global Change Biology, 2005)
Systematic, operational, long‐term observations of the terrestrial carbon cycle (including its interactions with water, energy and nutrient cycles and ecosystem dynamics) are important for the prediction and management of climate, water resources, food resources, biodiversity and desertification. To contribute to these goals, a terrestrial carbon observing system requires the synthesis of several kinds of observation into terrestrial biosphere models encompassing the coupled cycles of carbon, water, energy and nutrients. Relevant observations include atmospheric composition (concentrations of CO 2 and other gases); remote sensing; flux and process measurements from intensive study sites; in situ vegetation and soil monitoring; weather, climate and hydrological data; and contemporary and historical data on land use, land use change and disturbance (grazing, harvest, clearing, fire). A review of model–data synthesis tools for terrestrial carbon observation identifies ‘nonsequential’ and ‘sequential’ approaches as major categories, differing according to whether data are treated all at once or sequentially. The structure underlying both approaches is reviewed, highlighting several basic commonalities in formalism and data requirements. An essential commonality is that for all model–data synthesis problems, both nonsequential and sequential, data uncertainties are as important as data values themselves and have a comparable role in determining the outcome. Given the importance of data uncertainties, there is an urgent need for soundly based uncertainty characterizations for the main kinds of data used in terrestrial carbon observation. The first requirement is a specification of the main properties of the error covariance matrix. As a step towards this goal, semi‐quantitative estimates are made of the main properties of the error covariance matrix for four kinds of data essential for terrestrial carbon observation: remote sensing of land surface properties, atmospheric composition measurements, direct flux measurements, and measurements of carbon stores.